Dynamic right ventricular–pulmonary arterial uncoupling during maximum incremental exercise in exercise pulmonary hypertension and pulmonary arterial hypertension. (July 2019) - Singh, Inderjit; Rahaghi, Farbod N.; Naeije, Robert; Oliveira, Rudolf K.F.; Vanderpool, Rebecca R.; Waxman, Aaron B.; Systrom, David M.
Despite recent advances, the prognosis of pulmonary hypertension (PH) remains poor. While the initial insult in PH implicates the pulmonary vasculature, the functional state, exercise capacity, and survival of such patients are closely linked to right ventricular (RV) function. In the current study, we sought to investigate the effects of maximum incremental exercise on the matching of RV contractility and afterload (i.e. right ventricular–pulmonary arterial [RV–PA] coupling) in patients with exercise PH (ePH) and pulmonary arterial hypertension (PAH). End-systolic elastance (Ees), pulmonary arterial elastance (Ea), and RV–PA coupling (Ees/Ea) were determined using single-beat pressure-volume loop analysis in 40 patients that underwent maximum invasive cardiopulmonary exercise testing. Eleven patients had ePH, nine had PAH, and 20 were age-matched controls. During exercise, the impaired exertional contractile reserve in PAH was associated with blunted stroke volume index (SVI) augmentation and reduced peak oxygen consumption (peak VO2 %predicted). Compared to PAH, ePH demonstrated increased RV contractility in response to increasing RV afterload during exercise; however, this was insufficient and resulted in reduced peak RV–PA coupling. The dynamic RV–PA uncoupling in ePH was associated with similarly blunted SVI augmentation and peak VO2 as PAH. In conclusion, dynamic rest-to-peak exercise RV–PA uncoupling during maximum exercise blunts SV increase and reduces exercise capacity in exercise PH and PAH. In ePH, the insufficient increase in RV contractility to compensate for increasing RV afterload during maximum exercise leads to deterioration of RV–PA coupling. These data provide evidence that even in the early stages of PH, RV function is compromised.